Prediction Method of Bearing Life of Train Traction Motor Based on Preload Variation - HE Deqiang; ZHANG Huan; SUN Yi; MIAO Jian (机车电传动)
In order to predict the remaining working life of the bearing, the influence of traction motor bearing preload on bearing structure and dynamics characteristics was analyzed. In view of the individual bearing, the possible failure reasons and the corresponding preload characteristics of bearing were studied from the life stages. Through the ANSYS dynamics simulation analysis, it was concluded that the bearing natural frequency decreases with the preload decreases of the bearing. Based on the relationship between preload and bearing contact stress, a prediction method of bearing life based on preload variation was put forward. By monitoring the bearing vibration frequency to judge the change of the preload of bearings, the individual life of the traction motor bearings was predicted.